GLP-1 Receptor Agonists: Therapeutic Benefits in Renal Function, Cardiovascular Risk, and Physical Activity - A Systematic Review - Karaban, Łukasz; Kuźnieców, Tadeusz; Paszkowska, Monika; Mularczyk, Klaudia; Borawski, Michał; Ciuła, Aleksandra; Jakubiak, Anna; Miśkiewicz, Joanna; Znamirowska, Patrycja; Kupis, Magdalena (Quality in Sport, 2025)
Introduction: Type 2 diabetes is one of the greatest challenges of modern medicine. Its growing prevalence and numerous complications, especially cardiovascular ones, demand constant improvement of treatment strategies. Cardiovascular disease remains the leading cause of death in these patients, highlighting the importance of therapies that address both glycaemic control and cardiovascular risk. Aim of the study: This paper discusses the effects of GLP-1 receptor agonists (GLP-1 RA) and analyses recent data on their impact on cardiovascular risk, renal function, and interaction with physical activity. Key clinical trials and practical applications in daily practice are also presented. State of knowledge: GLP-1 RAs are well-established in the treatment of type 2 diabetes and obesity. They effectively lower glucose levels and reduce body weight while offering cardiovascular and nephroprotective benefits. Their role is particularly significant in patients with chronic kidney disease. Emerging data also suggest possible applications beyond diabetology, including neurology and cardiology. Material and methods: A PubMed search was conducted using relevant keywords for studies available up to March 2025. Only English-language publications were included. After title and abstract screening, full texts of eligible articles were analysed. Conclusions: GLP-1 RAs are a valuable part of therapy for patients with type 2 diabetes and obesity. They improve glycaemic control, support weight loss, and reduce cardiovascular and renal risk. Their safety profile allows for combination with other drugs. When used alongside physical activity, they can significantly enhance health outcomes and quality of life.